What is environmental politics? - DeSombre, Elizabeth R. 1966- (Polity, 2020)
"Scientific knowledge and technology alone cannot address environmental problems; they also involve difficult political choices and trade-offs both locally and globally. This concise introductory text explores the different ways in which society attempts to deal with the political decisions needed to prevent or recover from environmental damage"--
Keywords: Geschichte 1972-2015; Internationaler Umweltschutz; Umweltpolitik; Klimaschutz; Internationale Kooperation; Environmentalism / Political aspects; Environmental protection / Political aspects; Environmental policy